Optimization of Trade Product Inventory Using Activity Based Costing Analysis - Venus Khatta Salsabillah; Ni Luh Putu Hariastuti (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Merchandise inventory is one of the assets that requires significant capital investment. If inventory is not managed properly, it can result in high storage costs, the risk of inventory shortages, or even expired products. Therefore, it is important to have the right strategy in managing inventory. This study aims to classify inventory items owned by UD. XYZ in order to minimize inventory costs by focusing inventory procurement on high-value priority items. The method used in this study is Activity Based Costing analysis (ABC). The results of this study are based on the ABC classification there are 7 types of goods that fall into category A or priority are Aoka, Roma sandwich, My jelly, Slai olai, Trick, Choco pie, and Chiki balls. Where these 7 types of goods need special attention in terms of inventory management because they absorb the most investment funds from the total goods owned. By knowing these items, companies can focus on more precise inventory management, including in terms of procurement, storage, and inventory control. This can help UD. XYZ reduces unnecessary storage costs and ensures optimal availability of goods. The results of this study can contribute to the understanding of the application of the ABC method in the context of merchandise inventory management. Keywords: ABC Analysis, Classification, Inventory, Optimization